Identification of Mycobacterium kansasii by DNA hybridization. - Huang, Z H (1991)
A DNA probe specific for Mycobacterium kansasii was obtained from a plasmid clone library of EcoRI-digested genomic DNA. The probe specifically identified culture-confirmed isolates of M. kansasii and isolates in cultures of environmental water samples. In an attempt to distinguish between isolates of M. kansasii, we used two methods to demonstrate restriction fragment length polymorphisms in the genomic DNA. Both of these methods failed to detect any differences between the isolates. These isolates included the type strain TMC 1201, environmental isolates, and clinical isolates from Australia and the Solomon Islands. This result suggests that the genome of M. kansasii is highly conserved and that genetic divergence within this species in insignificant.